2013
DOI: 10.1128/jvi.00653-13
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of the Mumps Virus Phosphoprotein

Abstract: The phosphoprotein (P) is virally encoded by the Rhabdoviridae and Paramyxoviridae in the order Mononegavirales. P is a selfassociated oligomer and forms complexes with the large viral polymerase protein (L), the nucleocapsid protein (N), and the assembled nucleocapsid. P from different viruses has shown structural diversities even though their essential functions are the same. We systematically mapped the domains in mumps virus (MuV) P and investigated their interactions with nucleocapsidlike particles (NLPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(89 citation statements)
references
References 45 publications
2
86
1
Order By: Relevance
“…In a previous study, the MuV N protein was coexpressed with the P protein, and a ring of 13 subunits that packages random RNA inside was isolated (16). When the purified ring was stored for a few weeks at 4°C, it was found that the N protein was truncated after residue 379 (N 379 ) (24). The same truncation could be generated by trypsin treatment.…”
Section: Resultsmentioning
confidence: 85%
“…In a previous study, the MuV N protein was coexpressed with the P protein, and a ring of 13 subunits that packages random RNA inside was isolated (16). When the purified ring was stored for a few weeks at 4°C, it was found that the N protein was truncated after residue 379 (N 379 ) (24). The same truncation could be generated by trypsin treatment.…”
Section: Resultsmentioning
confidence: 85%
“…The self-association of P is required for transcriptional activity, and the binding site for SeV L was found to neighbor the oligomerization region (5,(7)(8)(9). Tetrameric P structures have also been observed for other paramyxoviruses, with crystallization of the P oligomerization domains being found for measles virus, human metapneumovirus, and mumps virus (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 85%
“…The last 49 amino acids (aa) of MuV P (aa 343 to 391) were found to directly mediate binding to the nucleocapsid through their interaction with the assembly domain of NP (27). This nucleocapsid-binding domain is conserved, but MuV P is unique in that the N-terminal domain also binds to the nucleocapsid (16). Electron microscopy revealed uncoiling of the helical nucleocapsid by the N-terminal domain of P, which resulted in enhanced viral RNA synthesis in a minigenome system (28).…”
mentioning
confidence: 99%
“…However, we considered this unlikely, since knockdown of Hsp72 showed little, if any, effect on MuV propagation in cultured cells. Recent studies revealed that the MuV P protein forms a unique tetramer structure different from those of other paramyxoviruses (31,32). Thus, MuV might differ from MV and RSV in the requirements for viral RNA replication and propagation.…”
Section: Discussionmentioning
confidence: 99%
“…However, Hsp72 was not essential for V protein degradation. The MuV P protein contains a multimerization domain at the unique C-terminal region and forms a homotetramer (31), while the V protein lacks the multimerization domain and functions as a monomer (42,43). The rate-limiting step of proteasomal degradation is the unfolding of substrates (44).…”
Section: Discussionmentioning
confidence: 99%